IMPLEMENTASI SINERGITAS TNI-POLRI DAN PEMERINTAH DAERAH GUNA PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN DALAM RANGKA TERCIPTANYA STABILITAS KEAMANAN DALAM NEGERI - Ismail, Zulkifli (Jurnal Abdi Insani, 2024)
Forest and land fires (karhutla) are a serious threat to the stability of domestic security, especially in vulnerable areas such as South Kalimantan. Handling forest and land fires requires strong synergy between the TNI, Police, and Local Government to prevent wider impacts on the environment, economy, and public health. This study aims to analyze the implementation of the synergy between the TNI, Polri, and Local Government in efforts to prevent forest and land fires and their contribution to the creation of domestic security stability. The approach used in this research is descriptive qualitative, by examining the strategies, as well as operational actions carried out by the three institutions. The results show that the synergy between the TNI, Polri and local government is very important in creating an early detection system, counseling to the community, and rapid response to fires. In addition, the success of forest and land fire prevention also depends on the quality and quantity of human resources, adequate infrastructure and budget. Within this framework, effective cooperation can improve disaster preparedness and mitigation, thereby preventing disruptions to security stability. Thus, integrated synergy between the TNI, Polri and local governments is not only important in forest and land fire prevention efforts, but also as an important pillar in maintaining sustainable domestic security stability. This research recommends increasing the capacity of human resources, modernizing infrastructure, and optimizing budget allocations as supporting factors for the successful implementation of synergy in handling forest and land fires.